Rationality versus brand loyalty a study of Harley-Davidson biker community in Poland - Rudnicki Adam (My University, 2008)
The aim of this paper is to identify the key to Harley-Davidson’s success on the American and European markets. The author analyzes the concept of brand associations and purchase motives to understand Harley-Davidson brand image and the loyalty it generates. He also investigates Harley-Davidson brand image in Poland by performing a survey among bikers and people who do not own a motorcycle. Both groups admire the classic design of Harley-Davidson motorcycles and bikers love the sound of its exhaust. The survey shows cruisers deliver the feeling of freedom and independence. Despite the fact there are only few models of large, heavyweight Harleys, each one of them is unique thanks to the modifications done by the users themselves. The author describes a typical Harley-Davidson user, as an educated, middle aged male from middle or higher social class. He recognizes the brand community as the key reason of an extreme brand loyalty towards the Harley-Davidson brand and he gives his own suggestions about the marketing activities the company should initiate to take full advantage of the growing demand for motorcycles in Poland.
Racjonalność czy lojalność wobec marki: badania społeczności użytkowników motocykli Harley-Davidson w Polsce
Keywords: marketing; brand; brand image; consumer behaviour; purchase motives